Improvement in Functional Outcomes After Elective Symptomatic Orthopaedic Implant Removal. (September 2020) - Williams, Benjamin R.; McCreary, Dylan L.; Parikh, Harsh R.; Albersheim, Melissa S.; Cunningham, Brian P.
Abstract : Introduction: The relative indications for removing symptomatic implants after osseous healing are not fully agreed on. The purpose of this study was to (1) determine whether patients showed improvement in functional outcomes after the removal of symptomatic orthopaedic implants, (2) compare the outcomes between upper and lower extremity implant removal, and (3) determine the rate of implant removal complications. Methods: A prospective study was conducted between 2013 and 2016. Patients completed a Short Musculoskeletal Function Assessment outcome questionnaire before implant removal and at the 6-month follow-up. Demographic data were stratified and compared between upper and lower extremity groups and between preimplant removal and 6-month postremoval. Results: Of the 119 patients included in the study, 85 (71.4%) were lower extremity and 34 (28.6%) were upper extremity. Significant improvement after implant removal was seen in the dysfunction index ( P ⩽ 0.001), bother index ( P ⩽ 0.001), and daily activities domain ( P ⩽ 0.001). Depression or anxiety ( P = 0.016) were statistically significant predictors for an improved Short Musculoskeletal Function Assessment dysfunction index score at 6 months. The complication rate was 10.1% (n=12) for the cohort. Discussion: Implant removal in both the upper and lower extremity presented notable improvement in dysfunction. Complications that require surgical intervention are extremely rare.